Prism adaptation overcomes pseudoneglect for the greyscales task - Loftus, Andrea; Vijayakumar, N.; Nicholls, M. (Elsevier, 2009)
Visuomotor adaptation to left-shifting prisms can affect performance for a variety of tasks in neurologically intact (normal) participants. This study examined whether visuomotor adaptation affects performance on the greyscales task in normal participants. Forty-two normal participants completed a greyscales task before and after adaptation to either: left-shifting prisms, right-shifting prisms or control spectacles that did not shift the visual scene. Participants demonstrated a leftward bias (i.e., selected the stimulus that was darker on the left as being darker overall) that was reversed by a short period of visuomotor adaptation to left-shifting prisms. In contrast, this bias was unaffected by adaptation toright-shifting prisms and control spectacles. The findings demonstrate that a simple visuomotortask can alter the distribution of spatial attention for the greyscales task in normal participants.